Extensive mucosal sloughing of the small intestine and colon in a patient with severe COVID‐19. Issue 1 (7th September 2021) - Yamakawa, Tsukasa; Ishigami, Keisuke; Takizawa, Ayumu; Takada, Yumemi; Ohwada, Sae; Yokoyama, Yoshihiro; Kazama, Tomoe; Hirayama, Daisuke; Yoshii, Shinji; Yamano, Hiro‐O; Ohizumi, Rina; Bunya, Naofumi; et al.
Abstract: Patients with coronavirus disease 2019 (COVID‐19) primarily cause respiratory symptoms. However, gastrointestinal (GI) symptoms can also occur. The endoscopic characteristics of the GI tract in COVID‐19 patients remain unclear. We herein report a 62‐year‐old male with severe COVID‐19 who needed multidisciplinary treatment, including extracorporeal membrane oxygenation (ECMO). Despite the improvement in his respiratory status, GI bleeding developed. Capsule endoscopy and colonoscopy revealed extensive mucosal sloughing in the lower intestinal tract. Additionally, we performed a comprehensive analysis of the mRNA expression levels of various proinflammatory cytokines in the intestinal mucosal tissues. The results suggested a significant elevation of IL‐6, which could be involved in the pathophysiology of the GI involvement in COVID‐19. Further investigation with more clinical data, including endoscopic findings and molecular analyses, will contribute to a comprehensive understanding of COVID‐19‐associated GI injury.